A Design Approach to Teaching an Entrepreneurial Mindset. Issue 1 (8th December 2019) - Mukhambetova, Aigerim; Camnert, Åsa Maria; Williams, Ariane
Abstract : The following research explores methods to develop an entrepreneurial culture with a growth mindset among adolescents, within the age bracket of 9 to 11 years old. In doing so, the proposal argues for the cultivation of an alternative learning experience that would not only challenge the rigorous hold of traditional academia over student imagination, but also acknowledge the impact of climate change, a surge in population growth, and high levels of automation, which, if left unaddressed, may jeopardize human ability to preserve capital and create long‐term sustained growth.